the best way to deal with the center of the ancient city of Najaf - محمد, م.م.ميساء ازيارة; صباح هادي, م.م احسان (Journal of Planner and Development, 2011)
The historic cities in the Arab and Islamic world (including the cities of the holy shrines in Iraq) suffer from many and varied problems and most notably it is clear in its origin functional structure. It had been transformed from a basic place to live for a few thousand of the population to the center or part of the main center of large city populations of more than one million. Functional structure of the ancient city have been change with the beginning of the twentieth century and accelerated rate of change in the second half of the last century. The research aims to analyze the problems of the historic centers of holy cities and analyze the methods of dealing with these problems, leading to discrimination method could be the basis for practical handling the according to the requirements of the current era and the requirements of the realities imposed by the changes and physical interventions with an attempt to salvage some of the fabric of these centers. The research had adopted the analytic inductive approach through the analysis of the existing case and look at previous studies of the subject and the literature on the themes of maintaining and dealing with historic and heritage sites. The research has been structuring to the entrance of the conceptual framework of the topic and other part is the analysis of existing conditions for the case study area (center the historic city of Najaf), according to a critical vision and reached to scientific and practical conclusions according to modern, planning and design vision to deal with traditional areas in general and the holy places in particular.